ETHICAL AND LEGAL CONSIDERATIONS IN SIMULATION-BASED MEDICAL TRAINING - Umida V.Turbanova; Zarina U.Salimova (Web of Journals Publishing, 2025)
Simulation-based medical training is a crucial tool for enhancing clinical skills, improving patient safety, and reducing medical errors. However, its integration into healthcare education presents significant ethical and legal challenges. This article explores key ethical concerns such as informed consent for students, trainees, and standardized patients, as well as the responsible use of real patient data in simulations. The psychological impact of high-fidelity scenarios, the use of cadavers and animal models, and the role of AI-based simulations are also examined. From a legal perspective, Slavinska et al. (2024) highlight the need for clear regulatory frameworks to ensure the responsible integration of simulation-based education into medical curricula. The importance of data protection laws and liability concerns in case of simulation-related errors is also emphasized. Budić et al. (2018) discuss moral and ethical dilemmas, particularly in balancing realism with ethical responsibility, while Ziv et al. (2000) argue that simulation is a powerful tool for improving patient safety when used within well-defined ethical guidelines. Additionally, Elendu et al. (2024) provide evidence of simulation's effectiveness in enhancing medical training outcomes, underscoring the need for structured institutional policies and accreditation standards. By addressing these challenges, medical institutions can develop legally compliant and ethically responsible simulation training programs. A structured approach will ensure that future healthcare professionals acquire essential skills while upholding ethical principles, patient safety, and legal integrity in medical education.
Keywords: Simulation-based medical training, patient safety, informed consent, data protection, medical ethics.